2021
DOI: 10.3390/molecules26164984
|View full text |Cite
|
Sign up to set email alerts
|

Current Status, Distribution, and Future Directions of Natural Products against Colorectal Cancer in Indonesia: A Systematic Review

Abstract: In 2020, an estimated 19.3 million new cancer cases and nearly 10 million cancer deaths have occurred worldwide, with colorectal cancer ranking as the third most frequently diagnosed (10.0%). Several attempts have been conducted against cancer, including surgery, radiation, monoclonal antibodies, and chemotherapy. Many people choose natural products as alternatives against cancer. These products will not only help in human life preservation but also work as a source of up-to-date information, leading people aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The Population, Intervention, Comparator, and Outcome (PICO) of the review was initially defined using an internationally accepted standard approach to systematic reviews [ 17 , 18 ]. Detailed descriptions of the PICO approach used in this systematic review are as follows: Population : Seaweed in Indonesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Population, Intervention, Comparator, and Outcome (PICO) of the review was initially defined using an internationally accepted standard approach to systematic reviews [ 17 , 18 ]. Detailed descriptions of the PICO approach used in this systematic review are as follows: Population : Seaweed in Indonesia.…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review's results are reported and presented following a standardized reporting methodology for systematic reviews of environmental studies [ 17 , 18 ] In addition to the report, a database comprising the results of the systematic review screening is provided.…”
Section: Methodsmentioning
confidence: 99%
“…Natural products are a rich source of anti-cancer reagents [ 12 ]. Shikonin (SHK) is the major chemical component of Lithospermum erythrorhizo , and has a broad range of pharmacological activities including anti-inflammatory, anti-oxidative stress, anti-virus, anti-bacteria, and anti-cancer effects [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is considered one of the major malignancies threatening the lives and health of people around the world. In 2020, more than 1.93 million additional CRC cases and 930,000 malignancy-related deaths worldwide were reported, accounting for 9.7% of all new cancer detections [ 1 ]. CRC is caused by factors related to lifestyle, diet, and genetic mutations [ 2 ].…”
Section: Introductionmentioning
confidence: 99%